MODERNISASI PENDIDIKAN ISLAM AWAL ABAD 20 (Studi Kasus di Sumatera Barat) - Rahman, Rini (Humanus, 2015)
The modernisation of Surau is marked by the start of Islamic Education institutions such as Sekolah Adabiyah, Sumatera Thawalib, Madrasah Diniyah, Madrasah Tarbiyah Islamiyah, and Normal Islam. These institutions apply a curriculum which includes both Islamic subjects as well as general subjects.The students graduating from these modern institutions bring positive influences to the development of Islamic education especially in West Sumatera.